(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
spinal tumor is a growth that develops within your spinal canal or within the bones of your spine. A spinal cord tumor, also called an intradural tumor, is a spinal tumor that that begins within the spinal cord or the covering of the spinal cord (dura). A tumor that affects the bones of the spine (vertebrae) is called a vertebral tumor.Spinal cord tumors may be classified as one of three different types depending on where they occur relative to the protective membranes of the spinal cord.